Pod upadającym nadzorem. Cenzura filmów polskich w latach 1986–1989 - Sowiński, Emil (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The article reconstructs the final three years of film censorship activities in the Polish People’s Republic. The author understands the term “censorship” not only as the activities of the Main Office for the Control of the Press, Publications and Performances but also of state cinema institutions. Therefore, the subject is both censorship interference in films and the programming policy of Polish People’s Republic-era cinema in relation to politically controversial films (documentaries and live-action films). The author situates his analysis in the political context (10th Congress of the Polish United Workers’ Party in 1986), institutional context (Cinema Act issued in 1987), and social context (the first elections in the Eastern Bloc that resulted in the communist government losing power, June 4, 1989).